2021
DOI: 10.1111/ppl.13316
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of water stress and salinity on growth, physiological, and biochemical traits in two walnut genotypes

Abstract: Due to its great economic value, walnut (Juglans regia L.) has received increasing attention during recent years. However, water stress and salinity limit walnut growth, production, and quality. We employed two walnut genotypes, precocious walnut, and late-bearing walnut, to investigate their growth, photosynthetic capacity, nonstructural carbohydrate contents, Cl − allocation, reactive oxygen species (ROS) accumulation, and osmotic regulation under water stress, salinity, and their combination.We found that l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 62 publications
3
29
0
Order By: Relevance
“…Our results showed that the enzymatic activity of SOD was higher in those leaflets showing 'medium' and 'severe' damage with values of 1.89-and 1.82-units min −1 g −1 , respectively (Table 3). This agrees with the results of Wang et al [7] in Juglans regia L. seedlings, irrigated with 50 mmol NaCl. The NaCl treatments (0, 300, 450 and 600 mmol) evaluated by Mohammadi et al [8] in Leptochloa fusca, indicate that the highest SOD enzymatic activity (4.0 U mg of protein) was observed in the 450 mmol treatment, which is associated with the ability of this species to buffer the negative effects of ROS.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Our results showed that the enzymatic activity of SOD was higher in those leaflets showing 'medium' and 'severe' damage with values of 1.89-and 1.82-units min −1 g −1 , respectively (Table 3). This agrees with the results of Wang et al [7] in Juglans regia L. seedlings, irrigated with 50 mmol NaCl. The NaCl treatments (0, 300, 450 and 600 mmol) evaluated by Mohammadi et al [8] in Leptochloa fusca, indicate that the highest SOD enzymatic activity (4.0 U mg of protein) was observed in the 450 mmol treatment, which is associated with the ability of this species to buffer the negative effects of ROS.…”
Section: Resultssupporting
confidence: 93%
“…The main areas for pecan production are in northern Mexico and the southeastern USA, where the irrigation tends to be either gravity fed or pumped [5]. The irrigation water is often high in salts, and these tend to be deposited as a crust on the soil surface because in these areas evaporation greatly exceeds precipitation [6,7]. Other factors that contribute to the accumulation of salts in soils are excessive applications of chemical fertilizers and inappropriate tillage, especially in clay soils with poor drainage [4].…”
Section: Introductionmentioning
confidence: 99%
“…The thin-shell walnuts in the Aksu area of Xinjiang have adequate quality and extensive market prospects. The genotypes of early-maturing and late-maturing walnuts were studied by Wang et al [ 6 ]. The authors analyzed the growth process, photosynthetic ability, and non-photosynthetic ability (carbohydrate content, chloride ion distribution, reactive oxygen species (ROS) accumulation, and osmotic adjustment under water stress, salinity, and their combination) of the two walnuts.…”
Section: Introductionmentioning
confidence: 99%
“…Drought or deficit irrigation is another major adverse abiotic stress that affects plant development. Water stress, like salinity stress, simulates physiological dehydration and results in low water potential and osmotic stress [ 10 ]. Water stress has a detrimental effect on plant development and yield, resulting in a cascade of morphological, biochemical, and physiological disturbances [ 11 , 12 ], particularly in arid and semi-arid zones, where evapotranspiration exceeds the annual precipitation, which results in an increase in salt levels in the near-surface soil layer [ 13 ].…”
Section: Introductionmentioning
confidence: 99%